2020
DOI: 10.1177/0741088320916508
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Revisions in Academic Text: Closing the Gap Between Process and Product Approaches in Digital Writing

Abstract: To date, research into dynamic descriptions of text has focused mainly on the spoken mode; and while writing process research has examined language structures, it has largely ignored the functionality (meaning) inherent in them. Therefore, drawing on systemic functional linguistics (SFL) and keystroke logging software, this article takes a further step toward an interdisciplinary dialogue by outlining a new schematic for coding and analyzing revisions. More specifically, we show how revision activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…In addition to addressing the limitations discussed above, future study could continue to examine the data collected in different ways. For example, analysis of revision patterns could examine whether patterns found by Bowen and Van Waes (2020) may extend to texting, analysis of the timing processes of morpho-phonological features, such as -t/-d or -ing deletion, may examine Einstein’s (2015) observations from Twitter data, and more detailed analysis of pause bursts may yield greater insight into how the psychomotor processes of composing on mobile devices may differ from writing on computer-based keyboards ( Mangen et al, 2015 ; Galbraith and Baaijen, 2019 ). Such analyses would necessarily expand upon the tools used for this study, requiring means to parse keystroke data in order to identify revision bursts and morphological features from keybursts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to addressing the limitations discussed above, future study could continue to examine the data collected in different ways. For example, analysis of revision patterns could examine whether patterns found by Bowen and Van Waes (2020) may extend to texting, analysis of the timing processes of morpho-phonological features, such as -t/-d or -ing deletion, may examine Einstein’s (2015) observations from Twitter data, and more detailed analysis of pause bursts may yield greater insight into how the psychomotor processes of composing on mobile devices may differ from writing on computer-based keyboards ( Mangen et al, 2015 ; Galbraith and Baaijen, 2019 ). Such analyses would necessarily expand upon the tools used for this study, requiring means to parse keystroke data in order to identify revision bursts and morphological features from keybursts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, participants in Leijten et al (2012) composed short simulated tweets; participants in Leijten et al (2015) composed texts typically written in under 10 min; participants in Van Waes et al (2010) revised short sentences; and participants in Nottbusch (2010) composed short sentences in response to stimuli. Even in studies that observed writers composing formal reports over multiple days, such as Leijten et al (2014) and Bowen and Van Waes (2020) , participants engaged in individual writing episodes that would last between 20 min to several hours. In other words, a study of writing on mobile devices, which may involve shorter forms of writing, may nevertheless yield similar data sets as Leijten et al (2014) and Bowen and Van Waes (2020) , in addition to involving writing more frequently throughout a participant’s everyday life.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations